2015
DOI: 10.4172/2332-2519.1000148
|View full text |Cite
|
Sign up to set email alerts
|

Are Radio Pulsars Extraterrestrial Communication Beacons?

Abstract: Evidence is presented that radio pulsars may be artificially engineered beacons of extraterrestrial intelligence (ETI) origin. It is proposed that they are beaming signals to various targeted Galactic locations including our solar system and that their primary purpose may be for interstellar navigation. More significantly, about half a dozen pulsars appear to be marking key sky locations that convey a message intended for our Galactic locale. One of these, the Millisecond Pulsar (PSR1937 + 21), appears to make… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 28 publications
(29 reference statements)
0
1
0
Order By: Relevance
“…He further suggested that the signal would likely broadcast isotropically, and be directed along the galactic plane. LaViolette (1999;2006; can be acknowledged for having speculated that pulsars may be artificial, and might also constitute a navigation system. Unfortunately, these claims are combined with mythology, commit fallacious probabilistic arguments, do not lead to specific predictions, and are uninformed by modern XNAV research (see also Vidal 2014, 250 for more critique).…”
Section: Is Seti-xnav New?mentioning
confidence: 99%
“…He further suggested that the signal would likely broadcast isotropically, and be directed along the galactic plane. LaViolette (1999;2006; can be acknowledged for having speculated that pulsars may be artificial, and might also constitute a navigation system. Unfortunately, these claims are combined with mythology, commit fallacious probabilistic arguments, do not lead to specific predictions, and are uninformed by modern XNAV research (see also Vidal 2014, 250 for more critique).…”
Section: Is Seti-xnav New?mentioning
confidence: 99%